Evaluating CHAT Seminars within a WebCT Networked Learning Environment - Pilkington, Rachel M.; Bennett, Catherine L. (Proceedings of the International Conference on Networked Learning, 2000)
An evaluation of a taught module "Learning and the New technologies" within a Post-Graduate Master of Education course "IT and Multimedia" is reported. The evaluation forms a case study of the use of Information and Communication Technology (JCT) to provide learning support for part-time, full-time and (potentially) distant students. Students on the course are mainly teachers learning for continuing professional development. A Virtual Learning Environment (VLE) was developed using WebCT and use of the environment was evaluated in relation to the quality of work produced by students and the nature of their interaction through the ICT tools. CHAT seminars discussed issues arising out of students' reading of set papers. These provided a reflective discussion forum to engage in Exploratory Dialogue. The evaluation of student use of the VLE raised the issue of how to increase the participation of some students .in on-line CHAT and group-work. Further issues included how to structure courses to meet the needs of full-time, part-time and distant students with different needs.